Rangeland ecology - Ericksen, Polly J.; Hiernaux, Pierre; Ayantunde, Augustine; Thornton, Philip K.; Sircely, Jason A.; Robinson, Lance W. (CAB International, 2020)
Rangelands research in arid and semi-arid sub-Saharan Africa has been reinvigorated by renewed government and donor interest in pastoral livelihoods. The challenges facing productive rangelands remain competition over resources, which has been exacerbated by armed conflict; overuse of some rangelands as fragmentation continues; and the failure of many technical and governance interventions. The unresolved development challenges of pastoralism in East and West Africa make it essential to renew long-term empirical research to understand rangeland dynamics and to develop appropriate public policies. The rangelands research agenda at the International Livestock Research Institue focuses on: (i) governance for better rangeland management; (ii) monitoring rangeland conditions to improve development interventions; (iii) understanding the interactions between climate change and the rangelands; and (iv) improving rangelands productivity for pastoral resilience.